Analysis of Interest Rate Policy on Bank Financial Performance - Hardiyanti, Siti Epa (PT Larva Wijaya Penerbit, 2024)
This research aims to analyze the influence of interest rate policy on bank financial performance in developing countries. Through case studies involving a number of large or representative banks in certain developing countries, historical data on interest rate policies and bank financial performance are collected and analyzed. Statistical and econometric methods, including linear regression, are used to evaluate whether changes in interest rate policy have a significant impact on banks' financial performance, including profitability, liquidity and credit growth. In addition, control variables such as bank size, capital structure, and macroeconomic conditions are taken into account in the analysis to ensure the accuracy of the results. This research aims to provide in-depth insight into the effectiveness of interest rate policy in regulating bank financial performance in developing countries and its implications for monetary policy and banking supervision.